Functional adaptation in Toll-like receptors of wild and domesticated animals - Fiddaman, S (2021)
Animals sense their pathogens through detection of conserved pathogen-associated molecules by pattern-recognition receptors (PRRs). The best characterised family of PRRs is the Toll-like receptors. TLR subfamilies retain specificity for particular agonist classes over great evolutionary distances. This does not, however, mean that TLRs are evolutionarily static. TLRs, along with other pathogen-facing immune genes, frequently undergo directional selection to maintain leverage in the perpetual arms race between hosts and pathogens.